THE STRUCTURE OF SPATIAL MATRICES FOR THE COMBINED OSCILLATIONS MULTIDIMENSIONAL ROD SYSTEMS - Raspopov, O. S. (Science and Transport Progress, 2008)
Dynamics of multicomponent rod systems with use of the theory of graphs and automatic machines is considered. It is shown that the structure of such models can be set by means of spatial matrices on the basis of research of topological properties of a system graph. In each case the possibility of realisation of the consecutive scheme by connections among themselves of typical logic elements is analyzed.